Factors Determining Athletic Footwear Design: A Case of Product Appearance and Functionality - Siriphan Promjun; Nopadon Sahachaisaeree (My University, 2012)
Footwear has currently been developed and tested by designers. Appearance is among the most important factors contributing to the popularity and market shares of particular brands and designs targeting on young purchasers. Using athletic footwear as a case study, the present research aims to investigate the pattern of footwear designs–shape, material, and type of shoe-base ergonomics and functionality. It is also bound to examine young purchasers' perceptions towards aesthetics The research finally recommends a set of design guidelines towards footwear design basing on purchesers' cognitive and affective perception on footwear appearance.
Keywords: Popularity; Lower Extremity Biomechanics and Pathologies